Pirfenidone Is a Vasodilator: Involvement of KV7 Channels in the Effect on Endothelium-Dependent Vasodilatation in Type-2 Diabetic Mice - Beck, Lilliana; Pinilla, Estéfano; Arcanjo, Daniel Dias Rufino; Hernanz, Raquel; Prat-Duran, Judit; Petersen, Asbjørn Graver; Köhler, Ralf; Sheykhzade, Majid; Comerma-Steffensen, Simon; Simonsen, Ulf (Frontiers in Pharmacology, 2021)
Endothelial cell dysfunction and fibrosis are associated with worsening of the prognosis in patients with cardiovascular disease. Pirfenidone has an antifibrotic effect, but vasodilatation may also contribute to the effects of pirfenidone. Therefore, in a first study, we investigated the mechanisms involved in the relaxant effect of pirfenidone in rat intrapulmonary arteries and coronary arteries from normal mice. Then in a second study, we investigated whether pirfenidone restores endothelial function in the aorta and mesenteric arteries from diabetic animals. From 16-18-week old normal male C57BL/6 mice and normoglycemic (db/db+), and type 2 diabetic (db/db) male and female mice, arteries were mounted in microvascular isometric myographs for functional studies, and immunoblotting was performed. In rat pulmonary arteries and mouse coronary arteries, pirfenidone induced relaxations, which were inhibited in preparations without endothelium. In mouse coronary arteries, pirfenidone relaxation was inhibited in the presence of nitric oxide (NO) synthase inhibitor, NG-nitro-L-arginine (L-NOARG), a blocker of large-conductance calcium-activated potassium channels (BKCa), iberiotoxin, and a blocker of KV7 channels, XE991. Patch-clamp studies in vascular smooth muscle revealed pirfenidone increased iberiotoxin-sensitive current. In the aorta and mesenteric small arteries from diabetic db/db mice relaxations induced by the endothelium-dependent vasodilator, acetylcholine, were markedly reduced compared to db/db+ mice. Pirfenidone enhanced the relaxations induced by acetylcholine in the aorta from diabetic male and female db/db mice. An opener of KV7 channels, flupirtine, had the same effect as pirfenidone. XE991 reduced the effect of pirfenidone and flupirtine and further reduced acetylcholine relaxations in the aorta. In the presence of iberiotoxin, pirfenidone still increased acetylcholine relaxation in the aorta from db/db mice. Immunoreactions for KV7.4, KV7.5, and BKCa channel subunits were unaltered in aorta from db/db mice. Pirfenidone failed to improve acetylcholine relaxation in mesenteric arteries, and neither changed acetylcholine-induced transient decreases in blood pressure in db/db+ and db/db mice. In conclusion, pirfenidone vasodilates pulmonary and coronary arteries. In coronary arteries from normal mice, pirfenidone induces NO-dependent vasodilatation involving BKCa and KV7 channels. Pirfenidone improves endothelium-dependent vasodilatation in aorta from diabetic animals by a mechanism involving voltage-gated KV7 channels, a mechanism that may contribute to the antifibrotic effect of pirfenidone.